The forgotten recipe - Clipston, Amy (Clipston, Amy. Amish heirloom novel, 2018)
Veronica Fisher is devastated when her fiance, Seth, is killed in an accident at work. Seth's friend, Jason Huyard, was with him and blames himself for Seth's death. Although Jason has never met Veronica, he feels as if he knows her because Seth talked about her constantly. After the accident, he can't seem to get Veronica out of his mind. Two months later, Veronica is cleaning the attic and comes across her mother's old hope chest. She finds an old recipe and soon discovers that baking helps her cope with her grief, so she opens a bake stand to sell her pies. Jason starts visiting the stand weekly, and their friendship grows, but Veronica isn't ready to court again. And Jason harbors his secret regret of not being able to save Seth. Veronica's mother must convince her that she can't completely give up on love. But when the truth is revealed, can Veronica forgive Jason for not telling her that he was there on that fateful day?